2020
DOI: 10.1007/s11307-020-01481-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring CD8a+ T Cell Responses to Radiotherapy and CTLA-4 Blockade Using [64Cu]NOTA-CD8a PET Imaging

Abstract: Purpose: Current response assessment systems for cancer patients receiving immunotherapy are limited. This is due to the associated inflammatory response that may confound the conventional morphological response evaluation criteria in solid tumors and metabolic positron emission tomography (PET) response criteria in solid. Recently, novel PET imaging techniques using radiolabeled antibodies and fragments have emerged as a particularly sensitive and specific modality for quantitative tracking of immune cell dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The patterns of activity retained in target brain regions of mice in the present studies are consistent with the hypothesis that M002 oHSV treatment mediated the specific retention of [ 89 Zr]-malDFO-169 cDb in the treated glioma tumors. The very low uptake of [ 89 Zr]-malDFO-169 cDb in normal brain regions was consistent with results from alternative radiolabeled polypeptide imaging agents that do not cross the BBB and show below 0.2% ID/g in normal brains of mice 40 , 41 . As all groups of mice received i.c.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The patterns of activity retained in target brain regions of mice in the present studies are consistent with the hypothesis that M002 oHSV treatment mediated the specific retention of [ 89 Zr]-malDFO-169 cDb in the treated glioma tumors. The very low uptake of [ 89 Zr]-malDFO-169 cDb in normal brain regions was consistent with results from alternative radiolabeled polypeptide imaging agents that do not cross the BBB and show below 0.2% ID/g in normal brains of mice 40 , 41 . As all groups of mice received i.c.…”
Section: Discussionsupporting
confidence: 80%
“…Our work adds to the growing body of studies that evaluate immunotherapy responses in vivo through immune cell-targeted PET imaging agents. Alternative CD8-targeted scaffolds (single-domain or F(ab)′2 antibody fragments) have shown correlations between PET signals and CD8 + cell infiltration as well as response to checkpoint immunotherapy in syngeneic murine non-CNS tumors 40 , 42 , 46 , 47 . A recent study showed that an anti-human CD8α-targeted minibody (IAB22M2C) labeled with 64 Cu specifically localized in orthotopic patient derived xenograft GBM tumors implanted in brain striatum of humanized mice; the PET signal in the tumor directly correlated with the number of human CD8 + cells that had trafficked into the tumors after systemic injection of human peripheral blood monocytes into the humanized mice 41 .…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the minibody has a fast blood clearance due to its small size, which allows for early image acquisition. A [ 64 Cu]labeled antibody was proposed for the in vivo quantification of CD8+ T cells as a prognostic biomarker in an immunocompetent mouse model of colorectal cancer [ 105 ] and breast [ 106 ] cancer. Since [ 64 Cu] has a shorter half-life (12.7 h) compared to [ 89 Zr] (78.4 h), the use of [ 64 Cu] reduces patient radiation exposure, thus improving the “acquisition window” compared to shorter-lived PET isotope such as [ 18 F] and [ 68 Ga].…”
Section: Molecular Imagingmentioning
confidence: 99%
“…To selectively target CD8+ T cells that mediate anti‐tumor cytotoxicity, researchers designed CD8‐targeted PET probes based on antibody fragments, such as minibodies, [ 122,148 ] diabodies, [ 50,52 ] single domain antibody (VHH), [ 51 ] and single chain variable fragments (scFv). [ 53 ] For instance, Rashidian et al. developed 89 Zr‐labeled anti‐CD8 VHH probes and showed that homogeneous CD8+ T cell infiltration throughout the tumor is associated with strong responses to immunotherapy across three tumor models.…”
Section: Identifying Predictive Biomarkers Of T Cell Responsementioning
confidence: 99%